The effect of hydrocotyle sibthorpioides lam. extract on dengue virus 2 inhibition in vitro - Husin, Fitrien (2015)
For thousands of years the practice of traditional medicine, using plant and herbs, has been effective in the treatment of various infections. Despite decades of efforts, there is no proven effective antiviral for DENV infection and attempts at vaccine development have been hampered by several major obstacles e.g different serotypes. The aim of this study therefore was to investigate the potential antiviral activity of Hydrocotyle sibthorpioides Lam. (H.sibthorpioides) towards DENV-2 infection in-vitro in three cell lines, Vero cells, C6/36 cells and HepG-2 cells. The H.sibthorpioides was extracted using two different solvents, water and methanol. Toxicity test were initially performed to evaluate and determine the highest tolerable dose of H.sibthorpioides extracts in the tested cell lines. The H.sibthorpioides methanolic extract was found to be more toxic than the water extract. Vero cells had a wider tolerance range to H.sibthorpioides extracts followed by C6/36 and HepG-2 cells. Antiviral assays were performed in two different stages, pre- and post-treatment to evaluate the H.sibthorpioides prophylactic and therapeutic effects on DENV-2 replication. The activities were scored by observing the morphological changes and CPE appearances, followed by detection of viral antigen by IFA and quantitation of viral titres by either plaque assay or qRT-PCR. The results demonstrated that H.sibthorpioides extracts possess mild prophylactic activity against DENV-2 replication in Vero cells but not in C6/36 cells. Pre-treatment of Vero cells showed that H.sibthorpioides pretreatment had 2 % - 44 % protective effect against DENV-2 in Vero cells using water extract, while 18 % - 30 % protective effect were seen when H.sibthorpioides methanolic extract was used. On the contrary, in general, H.sibthorpioides pre-treatment on C6/36 cells had low to no cellular protective effect against DENV-2 infection. Only few concentrations of H.sibthorpioides caused 5 % - 13 % inconsequential inhibition on C6/36 cells The post treatment of DENV-2 infected-Vero cells with H.sibthorpioides methanolic extract presented higher therapeutic effect when compared with the H.sibthorpioides water extract. The DENV-2 viral replication was inhibited by 6 % - 31 % when various concentrations of H.sibthorpioides water extract were used, while 2 % – 42 % of DENV-2 titre reduction was seen in Vero cells post treated with H.sibthorpioides methanolic extract. Surprisingly, post treatment of C6/36 cells resulted in an enhancement of DENV-2 replication. An enhancement effect of DENV-2 by 7 % - 59 % was seen in infected-C6/36 cells post treated with H.sibthorpioides water and methanolic extracts. The antiviral assay was further extended in HepG-2 cells and the results demonstrated that the methanolic extract of H.sibthorpioides was better than the water extract in reducing DENV-2 replication. Post treatment of H.sibthorpioides extracts against DENV-2 showed more potent antiviral activity followed by virucidal treatment and concurrent treatment in HepG2 cells. As a conclusion, H.sibthorpioides had variable effects on DENV-2 replication, depending on treatment types, solvent types and cell lines used; providing important novel insight on the phytomedicinal properties of the plant on DENV. Further studies are needed to verify which compounds could be responsible and how they exert their antiviral effects